Reputation: 4365
I'm studying continuations because I want to make some interesting use of coroutines... anyway, I want to better understand one implementation I found.
To do so I want to rewrite the implementation without using the computation expression (continuation Monad), but I'm not quite able to do it.
I have this:
type K<'T,'r> = (('T -> 'r) -> 'r)
let returnK x = (fun k -> k x)
let bindK m f = (fun k -> m (fun a -> f a k))
let runK (c:K<_,_>) cont = c cont
let callcK (f: ('T -> K<'b,'r>) -> K<'T,'r>) : K<'T,'r> =
fun cont -> runK (f (fun a -> (fun _ -> cont a))) cont
type ContinuationBuilder() =
member __.Return(x) = returnK x
member __.ReturnFrom(x) = x
member __.Bind(m,f) = bindK m f
member this.Zero () = this.Return ()
let K = new ContinuationBuilder()
/// The coroutine type from http://fssnip.net/7M
type Coroutine() =
let tasks = new System.Collections.Generic.Queue<K<unit,unit>>()
member this.Put(task) =
let withYield = K {
do! callcK (fun exit ->
task (fun () ->
callcK (fun c ->
tasks.Enqueue(c())
exit ())))
if tasks.Count <> 0 then
do! tasks.Dequeue() }
tasks.Enqueue(withYield)
member this.Run() =
runK (tasks.Dequeue()) ignore
// from FSharpx tests
let ``When running a coroutine it should yield elements in turn``() =
// This test comes from the sample on http://fssnip.net/7M
let actual = System.Text.StringBuilder()
let coroutine = Coroutine()
coroutine.Put(fun yield' -> K {
actual.Append("A") |> ignore
do! yield' ()
actual.Append("B") |> ignore
do! yield' ()
actual.Append("C") |> ignore
do! yield' ()
})
coroutine.Put(fun yield' -> K {
actual.Append("1") |> ignore
do! yield' ()
actual.Append("2") |> ignore
do! yield' ()
})
coroutine.Run()
actual.ToString() = "A1B2C"
``When running a coroutine it should yield elements in turn``()
So, I want rewrite the Put
member of the Coroutine class without using the computation expression K
.
I have read of course this and this and several other articles about catamorphisms but it is not quite easy to rewrite this continuation monand as it is to rewrite the Write Monad for example...
I try several ways, this is one of them:
member this.Put(task) =
let withYield =
bindK
(callcK (fun exit ->
task (fun () ->
callcK (fun c ->
tasks.Enqueue(c())
exit ()))))
(fun () ->
if tasks.Count <> 0
then tasks.Dequeue()
else returnK ())
tasks.Enqueue(withYield)
Of course it does not work :(
(By the way: there is some extensive documentation of all rules the compiler apply to rewrite the computation in plain F#?)
Upvotes: 3
Views: 147
Reputation: 5004
Your version of Put
is almost correct. Two issues though:
bindK
function is being used backwards, the parameters need to be swaped.task
should be passed a Cont<_,_> -> Cont<_,_>
, not a unit -> Cont<_,_> -> Cont<_,_>
.Fixing those issues it could look like this:
member this.Put(task) =
let withYield =
bindK
(fun () ->
if tasks.Count <> 0
then tasks.Dequeue()
else returnK ())
(callcK (fun exit ->
task (
callcK (fun c ->
tasks.Enqueue(c())
exit ()))))
tasks.Enqueue(withYield)
Of course it is not too elegant.
When using bind
it is better to declare an operator >>=
:
let (>>=) c f = bindK f c
that way
do!
translates to putting >>= fun () ->
after let! a =
translates to putting >>= fun a ->
after and then your code will look a little bit better:
member this.Put2(task) =
let withYield =
callcK( fun exit ->
task( callcK (fun c ->
tasks.Enqueue(c())
exit())
)
) >>= fun () ->
if tasks.Count <> 0 then
tasks.Dequeue()
else returnK ()
tasks.Enqueue withYield
Upvotes: 3